Severe acute bilateral alcohol-induced toxic optic neuropathy – case report - Wilczyński, Michał; Wilczyńska, Olena (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Toxic optic neuropathies are not frequently encountered in routine practice, however, they present a challenge both in terms of diagnosis and treatment. The aim of this paper is to present an unusual case of ethyl alcohol poisoning causing bilateral toxic optic neuropathy with loss of vision.